Green Investment and Emission Transparency Practices among IDX Consumer Non-Cyclicals from 2019 – 2024 - Astari Dianty; Kaca Dian Meila; Putri Gantine Lestari; Zihadi Dzikri Muchlisin; Zahra Yulianti (Journal of Business, Social and Technology, 2026)
Background: A company’s value is an important indicator for investors in assessing investment potential. In the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX), firm value has shown a downward trend, as indicated by market value as measured by Price-to-Book Value (PBV). Stakeholder demands extend beyond financial performance to include environmental responsibility, creating urgency for companies to adopt green investment practices and carbon emission transparency. Objective: This study aimed to analyze the relationship between carbon emission disclosure and green investment, both of which are believed to increase firm value. This research was conducted due to limited prior studies, inconsistent results in previous research, and a gap between theory and empirical practice. Methods: The research methodology employed was relevant and technical, using a sample of 78 financial statements from companies in the consumer non-cyclical sector that published sustainability reports and reported profitability during the study period from 2019 to 2024. Data validation techniques included classical assumption testing, path analysis, Cronbach’s coefficient (reliability) testing, t-hypothesis testing, and F-hypothesis testing. Results: Green investment has a significant and positive impact on firm value (t = 2.950, Sig. = 0.004). Carbon emission disclosure also has a significant and positive impact on firm value (t = 2.840, Sig. = 0.004). Simultaneously, both variables significantly explain variations in firm value (F = 6.550, Sig. = 0.003), with an explanatory power of R² = 14.7%. Conclusion: Green investment and carbon emission disclosure each increase firm value, both independently and jointly. Companies that invest in environmental sustainability and disclose their carbon footprint demonstrate responsibility to stakeholders, thereby increasing investor confidence and enhancing corporate valuation.